معوقات تطبيق الإدارة الإلكترونية في وزارة التربية والتعليم بسلطنة عمان(البوابة التعليمية الإلكترونية أنموذجاً) من وجهة نظر موظفي المديرية العامة لتقنية المعلومات (Journal Of Educational and Psychological Researches, 2017)
Drawbacks of Implementing Electronic Management in the Ministry of Education (A sample: Oman Educational Portal) from the Point of View of IT Staff. The study aimed at discovering the drawbacks of implementing electronic management in the Ministry of Education (a sample: Oman Educational Portal) from the point of view of IT staff, and that is by answering the following questions: - What are the main drawbacks (administrative, financial, technical and drawbacks related to human resources) that hinder implementing the electronic management in the Ministry of Education (a sample: Oman Educational Portal) from the point of view of IT staff? - Are there any statistical significance differences at the level (0.05) between study samples on the drawbacks of implementing the electronic management in the Ministry of Education (a sample: Oman Educational Portal) from the point of view of IT staff attributed to gender, academic qualifications, years of experience and the number of training courses? To answer the research's questions, the researcher used a questionnaire as her study tool. It consisted of 52 statements, and their credibility was confirmed by several experts. Cronbach's alpha was also used to confirm its reliability, and it scored (0.92). The study community consisted of all of IT staff (146 employee) in the Directorate General of Information Technology in the Ministry of Education in Muscat Governorate. The study sample was the study community itself. The researcher used the descriptive approach in her study. She also used the statistical methods like the arithmetic average, standard deviation, t-test and one-way analysis of variance to discover the significance level between variables. The most important results of the study are as follows: financial drawbacks took the first place among other drawbacks, and the other three drawbacks had very similar results. There were no statistical significance differences at the level (0.05) in all of the 4 drawbacks attributed to gender, academic qualifications and the number of training courses, but there were statistical significance differences at the level (0.05) in the administrative drawbacks attributed to years of experience (more than 10 years of experience). It was also found that there were statistical significance differences in the financial drawbacks (5 to 10 years of experience). In light of the results, the researcher recommended: providing adequate financial support to implement electronic management in the Ministry of Education and suitable training programmes for the staff responsible for implementing the electronic management. She also recommended creating a motivating system and linking it to the performance expected and the results of the actual implementation of the electronic management in the Ministry of Education.